1991
DOI: 10.1259/0007-1285-64-761-417
|View full text |Cite
|
Sign up to set email alerts
|

Non-ionic contrast media: a comparison of iodine delivery rates during manual injection angiography

Abstract: Iodine delivery rates (IDR) of five commonly used non-ionic contrast media were determined at room temperature (24 degrees C) and body temperature (37 degrees C). Contrast media of strength 300 mgI/ml were also evaluated at 50% dilution (150 mgI/ml) with N-saline. Iodine delivery differed significantly (p less than 0.005) between samples at room temperature: Omnipaque 350 (1163 mg/s) less than Niopam 370 (1311 mg/s) less than Omnipaque 300 (1422 mg/s) less than Niopam 300 (1635 mg/s) and Ultravist 300 (1636 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 3 publications
1
9
0
1
Order By: Relevance
“…Extrinsic warming of iodinated contrast material to 37°C reduces contrast material viscosity and has been advocated to decrease the frequency of adverse events related to intravenous administration (1)(2)(3)6,11,12 ) and to improve iodinated contrast material delivery ( 4,5 ). However, studies demonstrating effi cacy of a reduction in adverse risk from contrast material warming are scant, and the magnitude of demonstrable effect (when able to be shown at all [ 7 ]) has been small ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extrinsic warming of iodinated contrast material to 37°C reduces contrast material viscosity and has been advocated to decrease the frequency of adverse events related to intravenous administration (1)(2)(3)6,11,12 ) and to improve iodinated contrast material delivery ( 4,5 ). However, studies demonstrating effi cacy of a reduction in adverse risk from contrast material warming are scant, and the magnitude of demonstrable effect (when able to be shown at all [ 7 ]) has been small ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…The study was designed to include two study periods: (a) 200 days immediately prior to the cessation of extrinsic iodinated contrast material warming (to 37°C) at our institution (period 1, from March 14, 2010, through September 30, 2010) and (b) 200 days immediately after the cessation of contrast material warming (period 2, from October 1, 2010, through April 19, 2011). The use of contrast material warmers was discontinued at our institution on October 1, 2010, for all E xtrinsic warming of roomtemperature iodinated contrast material to human body temperature (37°C) is known to reduce contrast ma terial viscosity ( 1-4 ), and results of some studies ( 4,5 ) have shown that the practice can improve contrast material delivery rates with both hand and power injections through intravenous catheters. However, to our knowledge, only one study ( 6 ) has shown that warming iodinated contrast material prior to intravenous administration actually confers a reduction in the risk of adverse events (12% vs 10% for highosmolality contrast material [HOCM]).…”
Section: Subjectsmentioning
confidence: 99%
“…In the human knee and the ovine stifle, the meniscus, covering the tibial plateau and partially covering the femoral condyles, could prevent contrast to fully outline the cartilage. Passive mobilization of the joint and warming of the contrast medium (to enhance fluidity) are helpful to avoid this issue …”
Section: Discussionmentioning
confidence: 99%
“…Conversely, hand injections produced more variable flow; 3.5-6.0 ml/ sec in 6 F catheters, 1.8-3.0 ml/sec in 5 F catheters, and 1.4-2.0 ml/sec in 4 F catheters. Using forceful hand injections at 24 and 378C, Hughes and Bisset [23] studied iodine delivery rates through 5 F catheters with five different nonionic LOCM. Heating contrast agents produced a mean increase of 23% (range 20-27%) of delivery rate.…”
Section: Discussionmentioning
confidence: 99%